Management of a patient with joint syndrome (osteoarthrosis, gouty arthritis) : methodical recommendations for the preparation of students of higher education in the 6th year of study in the discipline «Internal Medicine» [Electronic resource] - Tykhonova, T. M.; Gorshunska, M. Yu.; Lysenko, N. V.; Bychkova, O. Yu.; Martymianova, L. O.; Soldatenko, I. V.; Barabash, N. Ye.; Тихонова, Т. М.; Горшунська, М. Ю.; Лисенко, Н. В.; Бичкова, О. Ю.; Мартим’янова, Л. О.; et al. (Kharkiv : V. N. Karazin Kharkiv National University, 2025)
The methodological recommendations specify the definition of joint syndrome and its diagnosis in rheumatic patients based on complaints, anamnesis, objective examination data and laboratory-instrumental diagnostics. Management of a rheumatic patient with joint syndrome is shown on the example of osteoarthritis and gouty arthritis. For students of the 6th year to prepare for practical classes in the discipline «Internal Medicine».

У методичних рекомендаціях наводиться визначення суглобового синдрому та його діагностика у ревматичних хворих за даними скарг, анамнезу, даних об’єктивного обстеження та лабораторно-інструментальної діагностики. На прикладі остеоартрозу та подагричному артриті показано ведення ревматичного хворого з суглобовим синдромом. Для студентів 6 курсу для підготовки до практичних занять з дисципліни «Внутрішня медицина».
Ведення пацієнта з суглобовим синдромом (остеоартроз, подагричний артрит)
Electronic educational publication for combined use. Can be used in local and network mode. In the author's edition
Keywords: SOCIAL SCIENCES::Social sciences::Education::Subject didactics; MEDICINE::Dermatology and venerology,clinical genetics, internal medicine::Internal medicine::Rheumatology; системні захворювання сполучної тканини; вузликовий періартеріїт; остеоартроз; подагричний артрит; системний червоний вовчак; глюкокортикоїди; нестероїдні протизапальні препарати; systemic connective tissue diseases; polyarteritis nodosa; osteoarthritis; gouty arthritis; systemic lupus erythematosus; glucocorticoids; nonsteroidal anti-inflammatory drugs